Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.21037/apm-21-573
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice of obesity among university students

Abstract: Background: Obesity, as an epidemic disease, is distributed among all age groups, including children, adolescents, adults, and the elderly. The goal of this study was to investigate the knowledge, attitude, and practice (KAP) concerning obesity among university students.Methods: In total, 1,317 questionnaires were filled out by 1,317 (466 male and 851 female) randomly selected students aged range from 16 to 24. All participants agreed to provide personal information in this study. A self-designed questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…From the responses received, 33.9% stated that, they consumed frequent snacks, 36.8% believed that, they had a typical body shape, and 44.6% desired to reduce their weight to remain physically fit. This study also showed that, most participants had a comparatively negative attitude towards PA in obesity management, which is a bit consistent with the present study 23 …”
Section: Discussionsupporting
confidence: 92%
“…From the responses received, 33.9% stated that, they consumed frequent snacks, 36.8% believed that, they had a typical body shape, and 44.6% desired to reduce their weight to remain physically fit. This study also showed that, most participants had a comparatively negative attitude towards PA in obesity management, which is a bit consistent with the present study 23 …”
Section: Discussionsupporting
confidence: 92%
“…However, college students’ dietary patterns, physical activity, as well as sedentary and other unhealthy lifestyle behaviors have coexisted and interacted with each other, thus increasing the risk of being overweight and obese, and being obese leads to a further decline in physical activity level [ 11 ]. There is also a general lack of awareness about obesity among college students, which increases the risk of obesity [ 12 ]. Clearly, a lack of exercise and obesity are major public health challenges.…”
Section: Introductionmentioning
confidence: 99%
“…The results in other countries are polarized with studies in China, Pakistan and India revealing cohorts who were knowledgeable on the core principles of obesity while studies done in the USA and United Kingdom (UK) showed otherwise. [14][15][16][17]20 The item that the respondents were most aware of is that BMI is a diagnostic tool for obesity. This is because BMI is commonly used and is regarded as the most useful population-level measure of overweight and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies involving students, employees and the general population revealed that these cohorts have ample knowledge on the basic concepts of obesity, specifically its risk factors. [14][15][16] However, one study highlighted the public's unawareness on the link of obesity to cancer. 17 Majority were also unfamiliar about treatment options and most do not try to prevent themselves from becoming obese.…”
Section: Methodsmentioning
confidence: 99%